The Predictor Factors Causing Length of Stay (LOS) in Diabetic Neuropathy Patients - Wahyuningsih, Marni; Rosyid , Fahrun Nur; Rahayuningsih, Faizah Betty (Poltekkes Kemenkes Palu, 2024)
Diabetes mellitus has emerged as a prevalent public health issue, experiencing a steady rise across the globe, in both developed and developing nations. Among the chronic complications frequently observed in diabetic individuals is diabetic neuropathy, characterized by recurrent infections, non-healing ulcers, and the potential for finger or toe amputations. These neuropathic complications often prolong the treatment duration, consequently impacting the length of hospitalization for patients. Neuropathic conditions in Type 2 Diabetes Mellitus (DM) result in a prolonged healing process. This research aims to analyze the predictor factors contributing to the Length of Stay (LOS) in neuropathic DM patients. It employs a quantitative research approach utilizing a descriptive correlation methodology. The research was conducted from October 2023 to February 2024 at Indriati Solo Baru Hospital, with a questionnaire serving as the research instrument. The sample in this research comprised patients with Diabetic Neuropathy (DM Neuropathy) selected using the Purposive Sampling technique and totaled 127 respondents. Data analysis included univariate, bivariate, and multivariate analyses. The outcomes revealed that out of the seven factors examined, only three factors were significantly associated with the Length of Stay (LOS) among neuropathic DM patients: control of blood sugar levels, presence of complications in respondents, and presence of comorbid diseases in respondents. The predictor factor that exerted the greatest influence on the Length of Stay (LOS) level in neuropathic DM patients was the presence of comorbid diseases in respondents. The study primarily focuses on identifying predictor factors for length of stay (LOS) in neuropathic DM patients. However, it did not thoroughly control for potential confounding variables that could influence LOS, such as socioeconomic status, access to healthcare, severity of neuropathy, and presence of other comorbidities aside from diabetes. suggestion to the next research to focus on other variables such as healthcare, the severity of neuropathy, and the presence of other comorbidities aside from diabetes.